Teknik Solution Focused Brief Counseling dalam Mengatasi Kebiasan Terlambat Siswa ke Sekolah - Muhammad Asbi; Sulaiman Samad; Rosmini Rosmini (Universitas Negeri Makassar, 2021)
The habit of students being late for school causes several negative impacts, these impacts greatly affect the teaching and learning process and furthermore will affect student learning outcomes making academic achievement decline. Group counseling service with a solution focused brief counseling approach with a total of 6 counselees is an activity design that will be implemented. Solution focused brief counseling is an approach based on the potential and strengths of the counselee that focuses on solutions and the future, carried out in a short time because the exploration of the problem becomes shorter. The goal is group counseling with a solution focused brief counseling approach to overcome students' tardiness. The results of group counseling activities show that the counselee is gradually changing, namely starting to arrive on time to school. Thus, it can be concluded that group counseling with a solution focused brief counseling approach can overcome the habit of being late for students at SMAN 7 Takalar.